Observation of CP violation in two-body B0(s)-meson decays to charged pions and kaons - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2021)
The time-dependent CP asymmetries of B0 → π+π− and $$ B_s^0 $$→ K+K− decays are measured using a data sample of pp collisions corresponding to an integrated luminosity of 1.9 fb−1, collected with the LHCb detector at a centre-of-mass energy of 13 TeV. The results are
Im Titel ist 0 hochgestellt und (s) tiefgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 03.05.2021